EFFECT OF LOCAL ANAESTHETICS ON ROHU FISH (LABEO ROHITA) IN LABORATORY CONDITION - BERA, PUJADEBI; SETT, PRITAM; GHOSH, TAPAS KUMAR (Journal of the Inland Fisheries Society of India, 2024)
Long distance transportation of fish seed is a serious problem. A good anesthetic will help to transport fish seed in healthy condition, decreases the rate of oxygen consumption and reduces the rate of excretion of carbon dioxide, ammonia and other toxic wastes along with transport cost and labor requirement. Anesthetics increase number of fish seed per container during transportation, avoid repeated thermal and mechanical shock. Ketamine and xylocaine were used as anesthetics @ 0.50 ml l-1, 0.75 ml l-1 and 1.0 ml l-1 on Labeo rohita fingerlings respectively. Application of anesthetics @ 0.75 ml l-1 and 1.0 ml l-1 decreased respiratory activity, ceased normal movement of fish. Little mortality (5-9%) was observed during transportation of fish seed exposed to ketamine and xylocaine respectively. Normal movement of ceased fish started after exposed to natural water. Ketamine can be used as an anaesthetic during fish seed transportation of Labeo rohita fingerlings and found to be more suitable than xylocaine @ 0.75 ml l-1 for a period upto 24 hours without any adverse effect either on fish behaviour or on mortality. The reduced metabolic activity in the anaesthetized fish leads to less consumption of oxygen; consequently, less release of carbon dioxide in the water thereby the fish seed do not get stressed as in the case of traditional fish seed transportation.